2022
DOI: 10.1037/apl0000856
|View full text |Cite
|
Sign up to set email alerts
|

Indexing dynamic collective constructs using computer-aided text analysis: Construct validity evidence and illustrations featuring team processes.

Abstract: Group for Organizational EffectivenessOrganizational processes have been widely recognized as both multilevel and dynamic, yet traditional methods of measurements limit our ability to model and understand such phenomena. Featuring a popular model of team processes advanced by Marks et al. (2001), we illustrate a method to use individuals' communications as construct valid unobtrusive measures of collective constructs occurring over time. Thus, the purpose of this investigation is to develop computer-aided text… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 77 publications
2
23
0
Order By: Relevance
“…As such, leveraging unobtrusive measurement may play a critical role. While studies utilizing traditional survey methods are able to index several instances of a given process, the use of computer-aided text analysis techniques or advanced analytics can allow for the creation of custom dictionaries which can index communications and interactions at nearly infinitely fine granularity (Cao et al, 2021; Mathieu et al, 2021). There are a number of possible ways to collect these streams of data (e.g., emails, video, activity, proximity trackers).…”
Section: Application Of Dynamic Team Compositionmentioning
confidence: 99%
“…As such, leveraging unobtrusive measurement may play a critical role. While studies utilizing traditional survey methods are able to index several instances of a given process, the use of computer-aided text analysis techniques or advanced analytics can allow for the creation of custom dictionaries which can index communications and interactions at nearly infinitely fine granularity (Cao et al, 2021; Mathieu et al, 2021). There are a number of possible ways to collect these streams of data (e.g., emails, video, activity, proximity trackers).…”
Section: Application Of Dynamic Team Compositionmentioning
confidence: 99%
“…Action processes might be best captured with trained observers coding recordings of teams playing, including conversations during timeouts or on the mound. Most recently, Mathieu et al (2021) introduce computer-aided text analysis (CATA) to score team processes using transcripts of team communications. They find that the robust methodology can serve as a practical way to capture and model multilevel, dynamic team process relationships over time.…”
Section: A Framework To Study Team Processes Using Sports Teamsmentioning
confidence: 99%
“…To, Kilduff, Ordonez, and Schweitzer (2018) provide one recent example of the use of data from physiological sensors on individual athletes in a laboratory setting to shed light on a phenomenon they observed using archival NFL data; we found very few other instances of data streams being used to measure dynamic concepts. As emerging technologies such as apps on personal cell phones, wearable devices and sensors, and computer-aided text analysis continue to be used across social science fields (Klonek et al, 2019; Luciano et al, 2018; Mathieu et al, 2021), work groups and teams researchers examining sports team samples will have a wide array of modalities from which to study team processes.…”
Section: Agenda For Future Researchmentioning
confidence: 99%
“…To date, with only a few exceptions (Larson et al, 2020;Mathieu et al, 2022) the temporal variations of transition and action processes have not been tested in models of existing research (e.g., Fisher, 2014; nor examined over multiple performance episodes (e.g., ). An exception is a study by Larson and colleagues (2020) who examined a single performance episode and found that student teams performed better when there was a steep increase in transition and action processes towards their deadline.…”
Section: Team Processes and Time: An Episodic Performance Perspectivementioning
confidence: 99%
“…Afterwards, teams are expected to shift their engagement to processes that directly contribute to accomplishing the team's goals (i.e., action processes; Marks et al, 2001). Even though Marks et al (2001, p. 361) in transition processes before working on task accomplishment facilitates action processes, while, contrarily, more recent studies found that teams performed better when they did not actively engage in transition processes early on in the performance episode (Larson et al, 2020;Mathieu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%